Preparation of the high power laser system PETAL for experimental studies of inertial confinement fusion and high energy density states of matter. (March 2016) - d'Humières, E.; Caron, J.; Perego, C.; Raffestin, D.; Dubois, J.-L.; Baggio, J.; La Fontaine, A. Compant; Hulin, S.; Ducret, J.-E.; Lubrano, F.; Gommé, J.C.; Gazave, J.; et al.
Abstract: The paper describes the preparation of the short-pulse high-energy laser PETAL that will be coupled to the French megajoule laser (LMJ) of CEA. The LMJ/PETAL facility will be opened to academic access for the international research community. In parallel diagnostics are being developed within the PETAL project and many physical problems are being addressed ranging from the study of the problems of radiation generation and activation issues to the problem of generation of large amplitude electromagnetic pulses.